Performance Evaluation of An Electrolyte-Supported Intermediate-Temperature Solid Oxide Fuel Cell (IT-SOFC) with Low-Cost Materials - Hary Devianto; Pramujo Widiatmoko; Isdiriayani Nurdin; Sung Pil Yoon; Tae-Hoon Lim; Aditya Farhan Arif; Fauzi Yusupandi (International Journal of Renewable Energy Development, 2022)
Intermediate temperature solid oxide fuel cell (IT-SOFC) provides economic and technical advantages over the conventional SOFC because of the wider material use, lower fabrication cost and longer lifetime of the cell components. In this work, we fabricated electrolyte-supported IT-SOFC using low-cost materials such as calcia-stabilized zirconia (CSZ) electrolyte fabricated by dry-pressing, NiO-CSZ anode and Ca3Co1.9Zn0.1O6 (CCZO) cathode produced through brush coating technique. According to the XRD result, the monoclinic phase dominated over the cubic phase, and the relative density of the electrolyte was low but the hardness of the CSZ electrolyte was close to the hardness of commercial 8YSZ electrolyte. The performance of the single cell was performed with hydrogen ambient air. An open-circuit voltage (OCV) of 0.43, 0.46, and 0.45 V and a maximum power density of 0.14, 0.50, and 1.00 mW/cm2 were achieved at the operating temperature of 600, 700, and 800 °C, respectively. The ohmic resistance of the cell at 700 and 800 °C achieved 81.5 and 33.00 Ω, respectively due to the contribution of thick electrolyte and Cr poisoning in electrodes and electrolyte